ISOLATION OF CHLOROPHYLL A FROM SPINACH (AMARANTHUS SPEC DIV.) AND ITS MODIFICATION USING FE2+ IN PHOTOSTABILITY STUDY AS OPTICAL MATERIALS - Ditya Sandiningtyas, Rachma
Chlorophyll is a natural pigment that is usually found in many green plants. Because of its structure that have conjugated double bonds, the chlorophyll can be explored its potential as an optical material. In this research, chlorophyll was isolated from leaves of spinach (Amaranthus Spec div.). The separation of chlorophyll a was conducted by using the sucrose column chromatography technique. The pure chlorophyll a then further modified by replacing the central ion of chlorophyll a, which is Mg2 + became Fe2+ to form Fe-pheophytin a. The optical characteristic and purity of chlorophyll a, pheophytin a, and Fe-pheophytin a were carried out using spectroscopic methods. The different characteristics of chlorophyll a and Fe-pheophytin a were distinguished from each other by the examination of their absorption and emission spectra. From absorbance measurements, there was a shift in the absorption peak of Fe-pheophytin a, which compared with chlorophyll a. The maxima of absorption of Fe-pheophytin a were observed at 393 nm in Soret band and 627 nm in Q band, while in the case of chlorophyll a were at 413 nm and 668 nm, respectively. Based on fluorescence measurement, it was observed that Fe-pheophytin a gives a red shift relatives to chlorophyll at 702.5 nm. The photostability of chlorophyll a and Fe-pheophytin a were studied by comparing the decay lifetime based on the fluoresescence measurement. Here, the decay lifetime of Fe-pheophytin a was observed 43.88 seconds, which is much longer than 12.79 seconds of chlorophyll a. This result suggests that Fe-pheophytin a is more stable intrisically than chlorophyll a.